All Our Brothers and Sisters Jews Saving Jews during the Holocaust - Baumel-Schwartz, Judith Tydor; Baumel-Schwartz, Judith Tydor; Schneider, Alan (Peter Lang, 2021)
The book focuses on the heroism of Jews throughout Europe who risked their lives to save their coreligionists under Nazi rule. The contributors discuss and analyze the actions of Jews who rescued other Jews from the hands of the Nazis. These actions took place, to different degrees, in Germany, in Axis states and all across Nazi-occupied Europe, from the early stages of persecution until the war$1 (Bs end, in the framework of collaborative efforts and individual initiatives. The Jews who rescued other Jews during the Holocaust came like their non-Jewish counterparts from different backgrounds: men and women, old and young, religious and secular, wealthy and poor, educated and uneducated. The rescue missions took place in ghettos, areas without ghettos, jails, camps, hospitals, children$1 (Bs homes, schools, monasteries, in hiding. This book focuses on these rescue missions and the people behind them, reminding us of their courage and willingness to act, even when it put their own lives in danger.s